The Effect of Leadership Style and Work Culture on Employee Performance Mediated by Job Satisfaction - Hasrul Hasra; Nurdin Brasit; Sumardi Lasise (Magister Management, Hasanuddin University, 2021)
This study aims at finding out the effect of leadership style and work culture on employee performance mediated by job satisfaction at Parepare-Owned Water Utility Company. In this study, the researcher applied a non-probability sampling technique collected using questionnaires totaling 60 employees. The obtained data were then analyzed using path analysis and the Sobel test. Results showed that leadership style and work culture had a direct and significant effect on employee job satisfaction. Both leadership style and work culture also show a direct and significant effect on employee performance. Job satisfaction had a direct effect on employee performance. Leadership style and work culture had an indirect and significant effect on employee performance mediated by job satisfaction.